Implementasi Media Pembelajaran Matematika Pada Anak Tunagrahita - Ulfatul 'Aliyah; Mokhamad Misbah; Agita Nabila Lestari; Ridho Ma'i Pratama; Nasikhotun Nadiroh (Tematik: Jurnal Pendidikan Dasar Islam, 2025)
The purpose of this study is to find out the learning media of adding mathematics to children with special needs with disabilities. This research is included in qualitative-descriptive research. The research was conducted using a qualitative method with a field research approach. Data collection techniques use observation, interviews and documentation. The results of the study showed that Mathematics learning activities for visually impaired children at SLB Kuncup Mas Banyumas on addition and subtraction materials using concrete media, namely colored pencils, leaves and stones. The three main factors that determine success in learning include students' intellectual abilities, learning strategies and the use of learning media.